CAKUPAN IMUNISASI BCG TERHADAP BAYI BARU LAHIR DI PROVINSI SUMATERA SELATAN - oom komalasari; Reni Oktarina (Dian Nuswantoro Semarang, 2019)
BCG immunization is a basic immunization given to reduce the risk of pulmonary TB. Children who are not immunized are at a risk of 1.13 times greater than those immunized. BCG immunization coverage in South Sumatra is 98.9%. This means that not all babies born with medical help get BCG immunization. Therefore it is necessary to do a study of the coverage of BCG immunization for newborns in South Sumatra. The purpose of this study was to determine the increase in the number of babies born, and increase the coverage of BCG immunization, as well as the distribution of districts in South Sumatra that meet BCG immunization coverage based on the number of babies born. This study uses a quantitative approach using descriptive statistical analysis methods. The variables analyzed in this study were the number of births and BCG immunization coverage. Data analysis continued with quadrant analysis to find out the distribution of districts based on immunization coverage rates and the number of babies born. The number of births of infants receiving medical assistance in South Sumatra tends to be stable with an average number of 9492.82 babies per district per year. The average percentage of BCG immunization coverage in South Sumatra tends to decrease, reaching 91.99% per district per year. The number of births of infants assisted by medical personnel has a very small relationship to BCG immunization coverage in South Sumatra Province which indicates that not every baby born with medical assistance receives BCG immunization. Based on quadrant analysis, it was found that there were 9 districts / cities that were included in Quadrant I & II which showed low BCG immunization rates. More specifically, there are 4 districts (Quadrant II) which have high rates of birth, but coverage of BCG immunization is low.